Key Function Words in a Corpus of UK Election Manifestos - Pearce, Michael (Linguistik Online, 2014)
This article explores a corpus of all the UK election manifestos produced by the three main political parties in the period 1900–2010. It offers an alternative perspective on function words in corpus-assisted critical discourse analysis, placing them at the centre rather than the periphery. Using a combination of WordSmith Tools and Sketch Engine, I identify four key function words and show how a consideration of their phraseological behaviour can – perhaps surprisingly – reveal aspects of party ideology, as well as pointing to generic change over time.